2019
DOI: 10.3389/fmicb.2019.00946
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Potential Virulence, and Population Diversity of Listeria monocytogenes From Meat and Meat Products in China

Abstract: Listeria monocytogenes is a globally notorious foodborne pathogen. This study aimed to qualitatively and quantitatively detect L. monocytogenes from meat and meat products in China and to establish their virulence profiles and population diversity. From 1212 meat and meat product samples, 362 (29.9%) were positive for L. monocytogenes . Of these positive samples, 90.6% (328/362) had less than 10 MPN/g, 5.5% (20/364) samples had 10–110 MPN/g, and 3.9% (14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 64 publications
6
28
1
Order By: Relevance
“…Serogroup IIa and IIb isolates have been the cause of most human listeriosis cases, according to a national foodborne disease surveillance network (Li et al, 2019). The serogroup IIa was the most prevalent serogroup in most foods in China (Chen et al, 2019;Zhang et al, 2019a), also IIa strains have shown extensive distribution on various foods around the world (Korsak et al, 2012;Wu et al, 2015). Similarly, serogroup IIa and IIb were most prevalent, in this study.…”
Section: Discussionsupporting
confidence: 66%
“…Serogroup IIa and IIb isolates have been the cause of most human listeriosis cases, according to a national foodborne disease surveillance network (Li et al, 2019). The serogroup IIa was the most prevalent serogroup in most foods in China (Chen et al, 2019;Zhang et al, 2019a), also IIa strains have shown extensive distribution on various foods around the world (Korsak et al, 2012;Wu et al, 2015). Similarly, serogroup IIa and IIb were most prevalent, in this study.…”
Section: Discussionsupporting
confidence: 66%
“… L. monocytogenes ST9 is rarely found in pig or ruminant farming environments, animals, or wild natural surroundings ( 22 , 58 60 ). This sequence type has, however, frequently been found to dominate in raw pork meat ( 21 , 52 , 61 ) and is also commonly found to persist in slaughterhouses ( 14 , 15 , 24 , 62 ) as well as in downstream compartments in the meat processing chain ( 10 , 22 , 26 ). In contrast, several studies report an absence or low abundance of ST9 in other food types and processing environments, such as fish/salmon, dairy, and fresh produce ( 22 , 26 , 31 , 47 , 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…The 27 isolated L. monocytogenes were tested for their resistance to 28 antibiotics belonging to 11 drug classes by the Kirby-Bauer disk diffusion antibiotic sensitivity testing using the breakpoints for Staphylococci [86] and interpreted according to the CLSI standards [87] or manufacturer's instructions.…”
Section: Antibiogram Profilementioning
confidence: 99%